VASALLO, B. (2021). Lenguaje inclusivo y exclusión de clase. Barcelona: Larousse. - Parra Rubio, Federico (Daimon Revista Internacional de Filosofia, 2024)
Reseña de VASALLO, B. (2021). Lenguaje inclusivo y exclusión de clase. Barcelona: Larousse.